Persepsi Petani Jagung (Zea mays Linn) Terhadap Kompetensi Penyuluh Pertanian di Desa Kaibon Kecamatan Ambal Kabupaten Kebumen - Trio Saputro; Istiko Agus Wicaksono; Didik Widiyantono (Universitas Muhammadiyah Purworejo, 2019)
This study aims to: (1) Determine the perceptions of corn farmers on the competency of agricultural instructors in Kaibon village, Ambal District, Kebumen Regency; (2) Find out what factors are related to the perception of corn farmers on the competency of agricultural instructors in Kaibon village, Ambal district, Kebumen district. The population in this study was all corn farmers in Kaibon village who tested 191 people. The study sample approved 66 people, determined by referring to, Yamane with an error rate of 10%. Sampling using a proportional random sampling technique. Data collection instruments using a questionnaire with a Likert scale. Data analysis uses the Spearman Rank revision. The results of the descriptive analysis in this study show that (1) the perception of corn farmers on the competency of agricultural instructors in program preparation, preparation of materials, media selection and application of methods in good categories, (2) using internal factors that connect corn farmers and external factors towards perception Corn farmers oppose the competency of agricultural instructors in program preparation, material preparation, media selection, and method application.